A CROSS-SECTIONAL CONTRIBUTION OF COMMUNITY CONSERVATION PRACTICES FOR IMPROVING MANAGEMENT OF KIBAALE NATIONAL PARK, SOUTH WESTERN UGANDA.: Biodiversity conservation - Nuwabimpa Rwiita, Milton; Tumwesigye, Wycliffe; Atwongyeire, Doreen (Student’s Journal of Health Research Africa, 2023)
Background: Deforestation and forest degradation are recognized as some of the primary causes of global warming, contributing to approximately 15% of global greenhouse gas emissions and thereby posing a significant challenge for climate change in East Africa. Kibale Forest National Park (KFNP) has experienced deforestation and degradation for numerous decades due to population pressure from neighboring communities whose livelihoods depend on crop production and livestock rearing adjacent to the forest. Despite its significance, documentation of community conservation practices surrounding KFNP has been inadequate. Therefore, the objective of this study was to establish the contribution of the local community to the conservation of and expansion of KFNP located in South Western Uganda. Methodology: A cross-sectional research design was employed, and a sample of 200 respondents from three parishes, namely Bigodi, Busiriba, and Kikoni, which border with KNP and lie along Kamwenge-Fort Portal Road, were selected. Data were collected using questionnaires and focus group discussions and analyzed through SPSS version 20. Results: The results indicate that community-based initiatives play a pivotal role in forest conservation, and the practices of local people aimed at enhancing their livelihoods and reducing illegal activities in the protected area, thereby promoting biodiversity conservation. Conclusion and recommendations: The study recommends that local communities should be actively involved in the policy formulation, planning, and management of KFNP. To reduce illegal activities and human-wildlife conflicts and enhance biodiversity conservation in KFNP, training in alternative sources of livelihood, strengthening law enforcement, and the provision of soft loans are recommended.